Current approaches to avoid the culling of day-old male chicks in the layer industry, with special reference to spectroscopic methods. (27th December 2017) - Krautwald-Junghanns, M-E; Cramer, K; Fischer, B; Förster, A; Galli, R; Kremer, F; Mapesa, E U; Meissner, S; Preisinger, R; Preusse, G; Schnabel, C; Steiner, G; et al.
Abstract: The negative correlation between fattening and laying performance prevents breeding improvement in both laying performance and meat yield. Therefore, specialized chicken lines have been bred in order to achieve either an efficient production of high-quality eggs or high growth rates. As a result, day-old male chicks are culled in the layer hatchery, which poses animal welfare and ethical problems. Breeding companies, scientific groups, and hatcheries are attempting to resolve this issue, with a common aim to find feasible alternatives for the routine killing of male layer chicks. Some approaches aim to influence the sex ratio, while others target at the economically feasible use of the male layer offspring, such as the fattening of "laying hen brothers" or crossbreedings of layers and broilers to create "dual-purpose chickens." Another approach is the sex determination prior to hatch. One of the prerequisites of in ovo sex determination is a practicable method that can be used in industry. The analysis needs to be rapid, cost-efficient, and highly precise; in addition, negative impacts on hatching rate, animal health, and/or performance parameters should be limited. Furthermore, sex determination should be performed before the sensory nervous system's response of the chick embryo to certain or potentially harmful stimuli is developed, which according to current knowledge is before the d 7 of incubation.